2020
DOI: 10.3390/genes11080844
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Copper Resistance in Acidithiobacillus Ferrivorans ACH Isolated from the Chilean Altiplano

Abstract: The use of microorganisms in mining processes is a technology widely employed around the world. Leaching bacteria are characterized by having resistance mechanisms for several metals found in their acidic environments, some of which have been partially described in the Acidithiobacillus genus (mainly on ferrooxidans species). However, the response to copper has not been studied in the psychrotolerant Acidithiobacillus ferrivorans strains. Therefore, we propose to elucidate the response mechanisms of A. ferrivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…It is mesophilic but able to grow at 4°C [30], as proven by its high abundance in culture RA5-4A (74.90%) and the remarkable performance of this culture in ferrous iron oxidation and ferric iron precipitation [4]. The genomic analysis of A. ferrivorans showed certain traits that might give this strain certain advantages compared to other Acidithiobacillus and could help to explain its prevalence in extreme environments like the Amarillo River; for instance it has multiple iron oxidation systems represented by the genes rusA (present in all Acidithiobacillus), rusB1, rusB2 (isoforms of rusticyanin) and iron periplasmic high potential iron-sulphur protein (HiPIP), an electron acceptor involved in ferrous iron oxidation in bacteria and the presence of genes associated with the oxidation of reduced sulphur compounds under denitrifying conditions ( [31], [32], [33]). Also, some strains of A. ferrivorans produce large amounts of EPS that contribute to the formation of bio lms and streamers [33] like the ones that can be seen in the Amarillo River (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is mesophilic but able to grow at 4°C [30], as proven by its high abundance in culture RA5-4A (74.90%) and the remarkable performance of this culture in ferrous iron oxidation and ferric iron precipitation [4]. The genomic analysis of A. ferrivorans showed certain traits that might give this strain certain advantages compared to other Acidithiobacillus and could help to explain its prevalence in extreme environments like the Amarillo River; for instance it has multiple iron oxidation systems represented by the genes rusA (present in all Acidithiobacillus), rusB1, rusB2 (isoforms of rusticyanin) and iron periplasmic high potential iron-sulphur protein (HiPIP), an electron acceptor involved in ferrous iron oxidation in bacteria and the presence of genes associated with the oxidation of reduced sulphur compounds under denitrifying conditions ( [31], [32], [33]). Also, some strains of A. ferrivorans produce large amounts of EPS that contribute to the formation of bio lms and streamers [33] like the ones that can be seen in the Amarillo River (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is mesophilic but able to grow at 4 °C [ 36 ], as proven by its high abundance in culture RA5-4A (74.9%) and the remarkable performance of this culture in ferrous iron oxidation and ferric iron precipitation [ 9 ]. The genomic analysis of A. ferrivorans showed certain traits that might give this strain certain advantages compared to other Acidithiobacillus and could help to explain its prevalence in extreme environments like the Amarillo River; for instance, it has multiple iron oxidation systems represented by the genes rusA (present in all Acidithiobacillus ), rusB1, rusB2 (isoforms of rusticyanin) and iron periplasmic high potential iron–sulphur protein (HiPIP), an electron acceptor involved in ferrous iron oxidation in bacteria and the presence of genes associated with the oxidation of reduced sulphur compounds under denitrifying conditions ([ 37 , 38 , 39 ]). Also, some strains of A. ferrivorans produce large amounts of EPS that contribute to the formation of biofilms and streamers [ 39 ], like the ones that can be seen in the Amarillo River ( Figure 1 h).…”
Section: Discussionmentioning
confidence: 99%
“…Since temperature can affect the behavior of microbial communities in the environment, becoming the limiting factor in bioleaching applications (Dopson et al, 2007;Xiao et al, 2017), efforts are being made in order to characterize bioleaching bacteria which can carry out its activity at low temperature and being therefore a good candidate for mining areas with low mean temperatures (Muñoz-Villagrán et al, 2022). While some of the isolated strains were able to grow at temperatures near 0°C, their Cu-resistance was low (1 mM) in comparison with strains isolated for biomining in previous studies (>100 mM) (Orell et al, 2010;Barahona et al, 2020). It is therefore suggested that the putative Cu-metabolizing microorganisms isolated might not be good candidates for bioleaching applications.…”
Section: New Metal(loid)-tolerance Insights Into Known Environmental ...mentioning
confidence: 99%